Review of Active Optical Sensors for Improving Winter Wheat Nitrogen Use Efficiency - Aula, Lawrence; Omara, Peter; Nambi, Eva; Oyebiyi, Fikayo B.; Raun, William R. (Agronomy, 2020)
Improvement of nitrogen use efficiency (NUE) via active optical sensors has gained attention in recent decades, with the focus of optimizing nitrogen (N) input while simultaneously sustaining crop yields. To the authors’ knowledge, a comprehensive review of the literature on how optical sensors have impacted winter wheat (Triticum aestivum L.) NUE and grain yield has not yet been performed. This work reviewed and documented the extent to which the use of optical sensors has impacted winter wheat NUE and yield. Two N management approaches were evaluated; optical sensor and conventional methods. The study included 26 peer-reviewed articles with data on NUE and grain yield. In articles without NUE values but in which grain N was included, the difference method was employed to compute NUE based on grain N uptake. Using optical sensors resulted in an average NUE of 42% ( 2.8% standard error). This approach improved NUE by approximately 10.4% (2.3%) when compared to the conventional method. Grain yield was similar for both approaches of N management. Optical sensors could save as much as 53 ( 16) kg N ha􀀀1. This gain alone may not be adequate for increased adoption, and further refinement of the optical sensor robustness, possibly by including weather variables alongside sound agronomic management practices, may be necessary.
Keywords: Active optical sensors; NUE; Nitrogen management; Winter wheat; Nitrogen